Analisis Persepektif Multi-Stakeholder terhadap Pengembangan Taman Kehati Hutan Pelawan dengan Konsep Healing Forest sebagai Inovasi Pariwisata Berkelanjutan - Dwi Rizky Cahyani; Rahman Rahman; Ega Apridian; Arian Syahri; Dwi Rizka Zulkia (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
This study aims to analyze the multi-stakeholder perspectives on the development of the Pelawan Forest Biodiversity Park (Taman Kehati Hutan Pelawan) through the healing forest concept as an innovation in sustainable tourism in Central Bangka Regency, Indonesia. A mixed-method approach was employed, combining interviews, observations, and questionnaires involving 45 respondents from local government, tourism managers, communities, and visitors. The findings indicate a high level of understanding and support toward the healing forest concept, with Likert scale scores ranging from 4.1 to 4.4, reflecting strong agreement on the integration of conservation-based and mental-wellness tourism. Environmental comfort and tourist interest in the healing concept emerged as the main factors promoting the site’s development potential. Stakeholder perspectives reveal aligned objectives among the government, community, and tourism actors to establish Pelawan Forest as an environmentally friendly quality tourism destination. This research emphasizes the importance of multi-stakeholder collaboration and sustainable governance to ensure tourism development that provides economic benefits while maintaining ecological balance and enhancing visitors’ mental and physical well-being.